Screening test for antibiotics in medicinal plants (STAMP): using powdered plant materials instead of extracts - Inácio, Marielle Cascaes [UNESP]; Carmona, Fabio; Paz, Tiago Antunes [UNESP]; Furlan, Maysa [UNESP]; Silva, Fernando Arcanjo da; Bertoni, Bianca Waléria; França, Suzelei de Castro; Soares, Ana Maria Pereira (Scientific Research Publishing, 2013)
Plants are a rich source of antibiotics, but screening all the existing plant species for biological activity using current methods can be time and resource consuming. The present study is to investigate whether powdered plant materials would perform as well as plant extracts in the screening of plants with antimicrobial activity. In the new method proposed (STAMP), we compared in vitro antimicrobial activity of powdered plant materials from 12 species against bacteria and fungi. We confirmed these results with their corresponding aqueous (wet) and hydro-alcoholic extracts and one species testing the antimicrobial activity of two isolated compounds. Compared with hydro-alcoholic extracts, screening using the powdered plant materials correctly identified the majority of the species with antimicrobial activity against Candida albicans (sensitivity 91%, specificity 86%), C. parapsilosis (sensitivity 100%, specificity 67%), and Staphylococcus aureus (sensitivity 64%, specificity 86%). For bacteria, the method performed better in a pH of 9.0. The antimicrobial activity of two compounds isolated from one species (maytenin and netzahualcoyone) confirmed the results. In conclusion, the use of powdered plant materials for screening plants with antimicrobial properties is a cheap, widely available, technically easy, time sparing, reproducible, and sensitive method and can significantly shorten the time and money spent during drug development.
Keywords: Herbal Drug; Botanical Drug; Phytotherapics; Natural Products